The Impact and Importance of Communication Within the Agricultural Units in Romania in the Digital Era - Ghinea, Raluca-Elena; Birsan, Alina Nicoleta; Vintila, Lorian; State, Cristina (European Journal of Sustainable Development, 2021)
The main objective of this paper is to analyse the degree of importance that the staff carrying out their activity within agricultural units in Romania gives to both internal and external organizational communication, and the impact, along with the implementations made, of the transition to the digital age. The research was quantitative, in the form of an online questionnaire, placed in a crowdsourcing system, distributed to the staff operating in agricultural units, holding both execution and management positions. It was filled in by 996 people, and the research started from the main idea that at local level, as well as institutional (ministry) level, there is still no concern for improving and enhancing professionalism and communication development, both externally as well as internally, in the context of the digital age we are experiencing. For an accuracy of the information, our analysis was based on 3 hypotheses. Testing the hypotheses based on obtained results led to the validation thereof and allowed us to draw up appropriate conclusions.